2014
DOI: 10.1186/1472-6823-14-24
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood manganese level with diabetes and renal dysfunction: a cross-sectional study of the Korean general population

Abstract: BackgroundThe purpose of this study was to evaluate the association between blood manganese levels and the prevalence of chronic diseases in the Korean population.MethodsThis was a cross-sectional study based on the Korean National Health and Nutrition Examination Survey (KNAHNES). The study included 3996 participants 20 years of age or older whose blood manganese levels had been measured. The participants were also evaluated for the presence of five chronic diseases: diabetes, renal dysfunction, hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 20 publications
1
40
1
Order By: Relevance
“…Chronic Mn accumulation in the mitochondria has been shown to affect MnSOD activity and could result in an abnormal response to the mechanism that blocks oxidative stress in the mitochondria and protects against endothelial dysfunction (Koh et al, 2014). However, presence or absence of properly functioning GST genes may influence the occurrence of oxidative stress, and subsequently influence the occurrence of mitochondrial damage, decrease effectiveness of antioxidants, and increase susceptibility to neurological and muscular diseases (Pagano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic Mn accumulation in the mitochondria has been shown to affect MnSOD activity and could result in an abnormal response to the mechanism that blocks oxidative stress in the mitochondria and protects against endothelial dysfunction (Koh et al, 2014). However, presence or absence of properly functioning GST genes may influence the occurrence of oxidative stress, and subsequently influence the occurrence of mitochondrial damage, decrease effectiveness of antioxidants, and increase susceptibility to neurological and muscular diseases (Pagano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified increased blood managese concentrations as a possible factor associated with oxidative stress (Erikson, Dobson, Dorman, & Aschner, 2004; Fernsebner, Zorn, Kanawati, Walker, & Michalke, 2014; Wu et al, 2010). On the other hand, Mn is an essential cofactor for metalloenzyme superoxide dismutase, which protects cells against antioxidant processes (Hope et al, 2006; Koh et al, 2014; Rucker, Thadhani, & Tonelli, 2010). Cells are also protected from oxidative stress by intracellular antioxidants like glutathione along with antioxidant enzymes like manganese superoxide dismutase (MnSOD) (Tamai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the aforementioned findings, manganese supplementation enhanced MnSOD activity and protected against T2D and diabetes complications (Burlet and Jain 2013; Lee et al 2013). However, with limited sample populations, several epidemiologic studies have yielded inconsistent associations between manganese levels and T2D (Kazi et al 2008; Koh et al 2014; Rambousková et al 2013). As a transition metal, manganese itself is an oxidant at high concentrations, and it appears to be involved in oxidative damage and mitochondrial dysfunction, which have been implicated in the development of T2D (Lowell and Shulman 2005; Maechler and Wollheim 2001).…”
Section: Introductionmentioning
confidence: 99%
“…23 Additional disease states hypothesized to play a role in Mn metabolism include renal dysfunction, diabetes, and metabolic syndrome. 37,38 However, these associations are less well documented and their modifying effects on parenteral nutrition Mn requirements or on the potential adverse effects of Mn are unclear.…”
Section: Disease Statesmentioning
confidence: 98%